Arabic type-making in the machine age : the influence of technology on the form of Arabic type, 1908-1993 - Nemeth, Titus. (Islamic Manuscripts and Books, 2017)
Arabic is the third most widely used script in the world, and gave rise to one of the richest manuscript cultures of mankind. Its representation in type has engaged printers, engineers, businesses and designers since the 16th century, and today most digital devices render Arabic type. Yet the evolution of the printed form of Arabic, and its development from metal to pixels, has not been charted before. Arabic Type-Making in the Machine Age provides the first comprehensive account of this history using previously undocumented archival sources. In this richly illustrated volume, Titus Nemeth narrates the evolution of Arabic type under the influence of changing technologies from the perspective of a practitioner, combining historical research with applied design considerations.